Suitability of the computer-assisted reading intervention Ekapeli Maahanmuutaja for preschool students with autism spectrum disorders : single-subject experimental piloting study - Kucharová, Petra (2021)
Individuals with autism spectrum disorders (ASD) show different aspects and severities of symptoms and comorbidities related to specific areas of learning. Children with ASD however have the potential to achieve full reading acquisition if provided with clear task and phonics instructions, and a suitable learning environment. The aim of this study is to investigate the usage and suitability of Ekapeli Maahanmuutaja, a computer-assisted reading intervention, in four Finnish preschool students with ASD. The data was collected via multiple methods, including questionnaires, Likert scale daily assessments, in-game log data, camera recordings, and eye movement tracking. A descriptive statistics method analysis was used in this study upon the transcription of the data based on the research questions. The findings indicate the potential suitability of the Ekapeli Maahanmuutaja computer-assisted reading intervention for preschool students with lower severity of ASD symptoms, such as the ability to use verbal communication. The participating students showed high levels of on-task behaviour and overall felt mostly satisfied with the intervention experience. Additionally, this study highlighted the individual variability in students with ASD and the connection between the severity of their symptoms and learning outcomes. The results of the study provided additional insights to the already existing information about the usage and effectiveness of the Ekapeli intervention in various groups of children, as well as underlined which used methods are potentially suitable for future research in this area.